Una aproximación cuantitativa en la incidencia del uso de marcadores en la redacción de la prensa deportiva: el Torneo Clausura 2107 a través del diario El Bocón - López Chumbe, Mark (2019)
The objective of this paper is to analyze the incidence of speech markers in the football journalistic writing of sports newspaper El Bocón during the 2017 Apertura tournament. The corpus consisted of the analysis of 104 newspapers, achieving the following results: they verified a total of 111 markers, of which 26 were identified as innovators, since they come from the Peruvian colloquial speech and fulfill the same function proposed by the inventory of Zorraquino and Portolés (1999). Likewise, it can be seen that the textual genre of the sports speech of the El Bocón newspaper for the 2017 Apertura Tournament, has essentially used connectors and, to a lesser extent, structuring and conversational markers. From these findings it is inferred that many of these discursive markers are more appropriate for certain text genres, in this case for the Peruvian sports writing.